Solve for x 3(2x-1)+5=6(x+1)

Math
3(2x-1)+5=6(x+1)
Simplify 3(2x-1)+5.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3(2x)+3⋅-1+5=6(x+1)
Multiply 2 by 3.
6x+3⋅-1+5=6(x+1)
Multiply 3 by -1.
6x-3+5=6(x+1)
6x-3+5=6(x+1)
Add -3 and 5.
6x+2=6(x+1)
6x+2=6(x+1)
Simplify 6(x+1).
Tap for more steps…
Apply the distributive property.
6x+2=6x+6⋅1
Multiply 6 by 1.
6x+2=6x+6
6x+2=6x+6
Move all terms containing x to the left side of the equation.
Tap for more steps…
Subtract 6x from both sides of the equation.
6x+2-6x=6
Combine the opposite terms in 6x+2-6x.
Tap for more steps…
Subtract 6x from 6x.
0+2=6
Add 0 and 2.
2=6
2=6
2=6
Since 2≠6, there are no solutions.
No solution
Solve for x 3(2x-1)+5=6(x+1)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top